La fusión glaciar en el Pirineo: condicionantes ambientales y primeros resultados bianuales en el glaciar de Infiernos (Pirineo aragonés) - Cancer Pomar, L.; Lampre Vitaller, F.; Ollero Ojeda, A.; Del Valle Melendo, J. (Geographicalia, 2016)
Data are presented about the environmental characters of the Infiernos glacier and of the regression suffered in the last century, as well as the meltwater flow values corresponding to two daily cycle of the Infierno glacier. These values were measured at the end of the summer of 1998 and 1999. There is a close relationship between these data and both thermic rythms. This fact suggests that meltwater flow should become a useful additional parameter to explain the environmental control of the drainage systems derived from the glacier fusion, as well as the serious glacier regression happened in the last decades, indicative of balances between the accumulation nival and the ablation clearly negative. The data are accompanied of measures of regression glacier among the summers of 1998 and 1999.
Keywords: glacier regression; meltwater flow; daily cycle; Pyrenean glaciers.